Analisis Efektivitas Kontribusi Pajak Restoran Sebagai Instrumen Fiskal Terhadap Pendapatan Asli Daerah Kota Medan Tahun 2020-2024 - Cindy Lira Fatika; Nurul Izzah Lubis (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the effectiveness of restaurant tax contributions as a fiscal instrument toward the Regional Original Revenue (PAD) of Medan City during the period of 2020–2024. This research employs a descriptive qualitative approach, utilizing secondary data from the Regional Revenue Agency (Bapenda) of Medan City and primary data obtained through in-depth interviews and field observations. Data analysis was conducted using the NVivo 15 Plus software to map the interrelationships between fiscal policies, restaurant business actors, and taxpayer compliance levels. The results indicate that the contribution of restaurant taxes to Medan City’s PAD averages around 4% per year, with the level of collection effectiveness fluctuating annually. The main challenges identified include low taxpayer awareness, limited field supervision, and technical issues in the online reporting system (e-SPTPD). On the other hand, the local government’s efforts through tax collection intensification programs, taxpayer education and socialization, as well as the implementation of digital reporting systems, have proven effective in improving reporting accuracy and transparency.This study emphasizes that the success of restaurant taxes as a source of regional revenue depends not only on fiscal policy and technology, but also on taxpayer compliance, tax literacy, and collaboration between local governments and business actors. These findings are expected to serve as valuable input for the Medan City Government in formulating more adaptive, effective, and sustainable regional tax strategies.